Direct but Not Indirect Methods Correlate the Percentages of Sperm With Altered Chromatin to the Intensity of Chromatin Damage - Ribas-Maynou, Jordi; Llavanera, Marc; Mateo-Otero, Yentel; Garcia-Bonavila, Estela; Delgado-Bermúdez, Ariadna; Yeste, Marc (Frontiers in Veterinary Science, 2021)
Although sperm chromatin damage, understood as damage to DNA or affectations in sperm protamination, has been proposed as a biomarker for sperm quality both in humans and livestock, the low incidence found in some animals raises concerns about its potential value. In this context, as separate methods measure different facets of chromatin damage, their comparison is of vital importance. This work aims at analyzing eight techniques assessing chromatin damage in pig sperm. With this purpose, cryopreserved sperm samples from 16 boars were evaluated through the following assays: TUNEL, TUNEL with decondensation, SCSA, alkaline and neutral sperm chromatin dispersion (SCD) tests, alkaline and neutral Comet assays, and chromomycin A3 test (CMA3). In all cases, the extent of chromatin damage and the percentage of sperm with fragmented DNA were determined. The degree of chromatin damage and the percentage of sperm with fragmented DNA were significantly correlated (P<0.05) in direct methods (TUNEL, TUNEL with decondensation, alkaline and neutral Comet) and CMA3, but not in the indirect ones (SCD and SCSA). Percentages of sperm with fragmented DNA determined by alkaline Comet were significantly (P<0.05) correlated with TUNEL following decondensation, and CMA3; those determined by neutral Comet were correlated with the percentage of High DNA Stainability (SCSA); those determined by SCSA were correlated with neutral and alkaline SCD, and those determined by neutral SCD were correlated with alkaline SCD. While, in pigs, percentages of sperm with fragmented DNA are directly related to the extent of chromatin damage when direct methods are used, this is not the case of indirect techniques. Thus, the results obtained herein differ from those reported for humans in which TUNEL, SCSA, alkaline SCD and alkaline Comet were found to be correlated. These findings may shed some light on the interpretation of these tests and provide some clues for the standardization of chromatin damage methods.